The Conformity of Al-Bay' bi al-Taqshīṭ Practices on Mobile Phone Credit Through Fintech Akulaku and Kredivo at Babat Counters with Sharia Principles and Regulations in Indonesia - Ifatun Nikmah; Holis; Ahmad Musadad; Shofiyun Nahidloh; Imamuddin bin Nahrawi (AL-IKTISAB: Journal of Islamic Economic Law, 2026)
The development of digital financial services has led to the increasingly widespread use of paylater facilities in consumer goods transactions, including mobile phone credit purchases through fintech platforms such as Akulaku and Kredivo, which are widely used at retail counters in Babat. Easy access, rapid processing, and minimal requirements make this practice attractive; however, its transactional structure raises issues related to cost transparency, late payment penalties, and compliance with sharia principles and national regulations. The main issue of this study concerns the form of mobile phone credit practices through these two fintech platforms and the extent to which their cost schemes, contractual arrangements, and penalty mechanisms align with the concept of al-bay’ bi al-taqshīṭ, the provisions of DSN-MUI Fatwas, and POJK No. 10/2022. This study aims to analyze the conformity of actual practices with sharia principles while also assessing their compliance with positive law. The research employs a qualitative method using an empirical juridical approach through the analysis of regulations, fatwas, academic literature, and in-depth interviews with counter employees and consumers using mobile phone credit services. The findings show that the transactions form a triangular scheme in which the counter merely supplies the goods, while all financing calculations, including additional charges and late payment penalties, are fully determined by the fintech system. Most consumers only understand the product price and installment amounts without being informed of the penalty structure, resulting in information asymmetry. The imposition of penalties as company revenue indicates non-compliance with sharia principles, as it closely resembles ribā nasī’ah, and does not fully meet OJK cost transparency standards. This study highlights the need to improve consumer education, contractual transparency, and penalty mechanisms so that paylater practices better reflect principles of justice and comply with sharia law and regulations.